P4.14 PREVALENCE OF DIASTOLIC LEFT VENTRICULAR DYSFUNCTION IN EUROPEAN POPULATIONS BASED ON CROSS-VALIDATED DIAGNOSTIC THRESHOLDS - M. Kloch-Badelek*; T. Kuznetsova; W. Sakiewicz; V. Tikhonoff; A. Ryabikov; M. Loster; K. Stolarz-Skrzypek; L. Thijs; K. Narkiewicz; J. Staessen; K. Kawecka-Jaszcz; D. Czarnecka (Artery Research, 2015)
Objective: Different diagnostic criteria limit comparisons between populations in the prevalence of diastolic left ventricular (LV) dysfunction. We aimed to compare across populations age-specific echocardiographic criteria for diastolic LV dysfunction as well as their correlates and prevalence. Methods: We measured the E and A peaks of transmitral blood flow by pulsed wave Doppler and the e′ and a′ peaks of mitral annular velocities by tissue Doppler imaging (TDI) in 2 cohorts randomly recruited in Belgium (n = 782; 51.4% women; mean age, 51.1 years) and in Italy, Poland and Russia (n = 476; 55.7%; 44.5 years). Results: In stepwise regression, the multivariable-adjusted correlates of the transmitral and TDI diastolic indexes were similar in the 2 cohorts and included sex, age, body mass index, blood pressure and heart rate. Similarly, cutoff limits for the E/A ratio (2.5th percentile) and E/e′ ratio (97.5th percentile) in 338 and 185 reference subjects free from cardiovascular risk factors respectively selected from both cohorts were consistent within 0.02 and 0.26 units (median across 5 age groups). The rounded 2.5th percentile of the E/A ratio decreased by ∼0.10 per age decade In these apparently healthy subjects. The reference subsample provided age-specific cut-off limits for normal E/A and E/e′ ratios. In the 2 cohorts combined, diastolic dysfunction groups 1 (impaired relaxation), 2 (possible elevated LV filling pressure) and 3. Conclusion: The age-specific criteria for diastolic LV dysfunction were highly consistent across populations with an age-standardized prevalence of 22.4% vs. 25.1% (P=0.09).